Experimental analysis and modelling of bond formation in ultrasonic heavy wire bonding - Schemmel, Reinhard; Scheidemann, Claus; Hemsel, Tobias; Kirsch, Olaf; Sextro, Walter (CIPS 2020; 11th International Conference on Integrated Power Electronics Systems)
Ultrasonic wire bonding is a process to form electrical connections in electronics well established industry. Typically, a clamping tool is pressed on the wire and forced to vibrate at relative high frequency 40 to 100 kHz. The ultrasonic vibration is transmitted through the wire into the interface between wire and substrate. Due to frictional processes, contamination like oxide layers are removed from the contact zone, the surface roughness is reduced, and with increasing bond duration an metallic connection of wire and substrate is established. It is known that the amount of ultrasonic energy over time directly influences the strength and reliability of the bond connection, but the determination of optimum bond parameters is still a challenging experimental task. For this, in the past different model approaches have been presented, to calculate the bond quality by simulation. Measuring the friction between wire and substrate to validate these models is a challenging task at ultrasonic bonding frequency. Therefore a versatile test rig for bonding experiments at frequencies lower than 1 kHz is setup to get detailed insight into the different phases of the connection process. It includes a piezoelectric force sensor for the measurement of the three-dimensional process forces, an electrodynamic shaker for the vibration excitation and a conventional tension-compression testing machine to apply the bond normal force. Using this test rig, it is possible to observe the different phases of bond formation in detail, validate and enhance existing models and finally optimize bond parameters for different processes.

Schwingungen - Magnus, Kurt; Popp, Karl; Sextro, Walter
Schwingungsprobleme in der Technik analysieren, verstehen und beschreiben Schwingungen treten als nützliche oder auch als störende Erscheinungen fast überall in Natur und Technik auf. Deshalb ist es wichtig, sie zu verstehen, zu deuten oder auch in gewünschter Weise zu beeinflussen. Dieses Lehrbuch gibt eine Einführung in die physikalischen Grundlagen und die mathematische Behandlung von Schwingungen. In der aktuellen Auflage wurden der Text und die Bilder überarbeitet sowie konstruktive Hinweise von Fachkollegen berücksichtigt. Der Inhalt Grundbegriffe und Darstellungsmittel - Freie Schwingungen - Selbsterregte Schwingungen - Parametererregte Schwingungen - Erzwungene Schwingungen - Koppelschwingungen - Kontinuumsschwingungen - Chaotische Bewegungen - Aufgaben und Ergebnisse Die Zielgruppe Studierende der Ingenieurwissenschaften, der Physik und der Mathematik, berufstätige Ingenieure

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (2020 21st International Conference on Thermal, Mechanical and Multi-Physics Simulation and Experiments in Microelectronics and Microsystems (EuroSimE))

Evaluation of time series forecasting approaches for the reliable crack length prediction of riveted aluminium plates given insufficient data - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (PHM Society European Conference)
In all fields, the significance of a reliable and accurate predictive model is almost unquantifiable. With deep domain knowledge, models derived from first principles typically outperforms other models in terms of reliability and accuracy. When it may become a cumbersome or an unachievable task to build or validate such models of complex (non-linear) systems, machine learning techniques are employed to build predictive models. However, the accuracy of such techniques is not only dependent on the hyper-parameters of the chosen algorithm, but also on the amount and quality of data. This paper investigates the application of classical time series forecasting approaches for the reliable prognostics of technical systems, where black box machine learning techniques might not successfully be employed given insufficient amount of data and where first principles models are infeasible due to lack of domain specific data. Forecasting by analogy, forecasting by analytical function fitting, an exponential smoothing forecasting method and the long short-term memory (LSTM) are evaluated and compared against the ground truth data. As a case study, the methods are applied to predict future crack lengths of riveted aluminium plates under cyclic loading. The performance of the predictive models is evaluated based on error metrics leading to a proposal of when to apply which forecasting approach.
Keywords: PHM 2019; crack propagation; forecasting; unevenly spaced time series; step ahead prediction; short time series

Model-Based Investigation of the Influence of Wheel Suspension Characteristics on Tire Wear - Schütte, Jan; Sextro, Walter (Lecture Notes in Mechanical Engineering)

Evaluating FPGA Accelerator Performance with a Parameterized OpenCL Adaptation of Selected Benchmarks of the HPCChallenge Benchmark Suite - Meyer, Marius; Kenter, Tobias; Plessl, Christian (2020 IEEE/ACM International Workshop on Heterogeneous High-performance Reconfigurable Computing (H2RC))
FPGAs have found increasing adoption in data center applications since a new generation of high-level tools have become available which noticeably reduce development time for FPGA accelerators and still provide high-quality results. There is, however, no high-level benchmark suite available, which specifically enables a comparison of FPGA architectures, programming tools, and libraries for HPC applications. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community.
Keywords: FPGA; OpenCL; High Level Synthesis; HPC benchmarking

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Patent EP 3 358 332 B1: Verfahren zur Bestimmung des Beginns einer verschleißbedingten Bauteil-Restnutzungsdauer eines elastisch verformbaren Bauteils, als Strukturteil und/oder Lagerteil eines Geräts. - Reinke, Kai; Bender, Amelie; Meyer, Tobias; Sextro, Walter; Kimotho, James Kuria
Die Erfindung betrifft ein Gerät mit wenigstens einem elastisch verformbaren Bauteil als Strukturteil und/oder Lagerteil, auf das im Betriebsverlauf von wechselnden Betriebszuständen abhängige, unterschiedliche Verformungskräfte einwirken, die zu einem die Bauteilnutzungsdauer begrenzenden Bauteilverschleiß führen, und mit einer Einrichtung zur Bestimmung der Bauteilnutzungsdauer und einer verschleißbedingten Bauteil-Restnutzungsdauer. Erfindungsgemäß wird ein sich zeitversetzt wiederholender, jeweils gleicher Betriebszustand vorbestimmt, dem eine jeweils gleiche Verformungskraft zugeordnet ist, durch die das elastisch verformbare Bauteilmaterial verformt wird. Ein solcher vorbestimmter Betriebszustand wird jeweils von einer Mess- und Auswerteeinheit erkannt und ein Messvorgang durch ein Startsignal selbsttätig gestartet, wobei mit wenigstens einem bauteilzugeordneten Beschleunigungssensor, die aktuelle Beschleunigung der Verformung oder daraus abgeleitete Kennwerte als Kenngröße für eine aktuelle Bauteilsteifigkeit gemessen und jeweils in einer Messkurve gespeichert und verglichen wird.

The Welfare Conventions Approach: A Comparative Perspective on Social Impact Bonds - Chiapello, Eve; Knoll, Lisa (Journal of Comparative Policy Analysis: Research and Practice)
Keywords: Public Administration; Sociology and Political Science

Social Finance and Impact Investing: Governing Welfare in the Era of Financialization - Chiapello, Eve; Knoll, Lisa (Historical Social Research)

Re/Dissolving Mimesis

A CCTV Image that Dissolves like Smeared Data: Distinguishability versus Similarity - Althoff, Sebastian (Re/Dissolving Mimesis)

Editorial: Re/Dissolving Mimesis - Althoff, Sebastian; Linseisen, Elisa; Müller, Maja-Lisa; Winter, Franziska (Re/Dissolving Mimesis)

Seeping Out: The diminishment of the subject in Hito Steyerl’s How Not to Be Seen - Althoff, Sebastian (Performance Research)

Oracle complexity classes and local measurements on physical Hamiltonians - Gharibian, Sevag; Piddock, Stephen; Yirka, Justin (Proceedings of the 37th Symposium on Theoretical Aspects of Computer Science (STACS 2020))
The canonical problem for the class Quantum Merlin-Arthur (QMA) is that of estimating ground state energies of local Hamiltonians. Perhaps surprisingly, [Ambainis, CCC 2014] showed that the related, but arguably more natural, problem of simulating local measurements on ground states of local Hamiltonians (APX-SIM) is likely harder than QMA. Indeed, [Ambainis, CCC 2014] showed that APX-SIM is P^QMA[log]-complete, for P^QMA[log] the class of languages decidable by a P machine making a logarithmic number of adaptive queries to a QMA oracle. In this work, we show that APX-SIM is P^QMA[log]-complete even when restricted to more physical Hamiltonians, obtaining as intermediate steps a variety of related complexity-theoretic results. We first give a sequence of results which together yield P^QMA[log]-hardness for APX-SIM on well-motivated Hamiltonians: (1) We show that for NP, StoqMA, and QMA oracles, a logarithmic number of adaptive queries is equivalent to polynomially many parallel queries. These equalities simplify the proofs of our subsequent results. (2) Next, we show that the hardness of APX-SIM is preserved under Hamiltonian simulations (a la [Cubitt, Montanaro, Piddock, 2017]). As a byproduct, we obtain a full complexity classification of APX-SIM, showing it is complete for P, P^||NP, P^||StoqMA, or P^||QMA depending on the Hamiltonians employed. (3) Leveraging the above, we show that APX-SIM is P^QMA[log]-complete for any family of Hamiltonians which can efficiently simulate spatially sparse Hamiltonians, including physically motivated models such as the 2D Heisenberg model. Our second focus considers 1D systems: We show that APX-SIM remains P^QMA[log]-complete even for local Hamiltonians on a 1D line of 8-dimensional qudits. This uses a number of ideas from above, along with replacing the "query Hamiltonian" of [Ambainis, CCC 2014] with a new "sifter" construction.

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Characterisation of width-dependent diffusion dynamics in rubidium-exchanged KTP waveguides - Padberg, Laura; Santandrea, Matteo; Rüsing, Michael; Brockmeier, Julian; Mackwitz, Peter; Berth, Gerhard; Zrenner, Artur; Eigner, Christof; Silberhorn, Christine (Optics Express)

Resource‐Efficient Low‐Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation - Tan, Deming; Kirbus, Benjamin; Rüsing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M. (Small)
Optically nonlinear Pb2B5O9X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo‐) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low‐cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb 2 B 5 O 9 X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite‐like borate halide structure. Thorough examinations using powder X‐ray diffraction and scanning electron microscopy, the Pb2B5O9X microcrystals are indicated to be chemically pure and single‐phased. Besides, the Pb2B5O9X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low‐temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo‐) catalysis investigations.
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Shallow-etched thin-film lithium niobate waveguides for highly-efficient second-harmonic generation - Zhao, Jie; Rüsing, Michael; Javid, Usman A.; Ling, Jingwei; Li, Mingxiao; Lin, Qiang; Mookherjea, Shayan (Optics Express)
High-fidelity periodic poling over long lengths is required for robust, quasi-phase-matched second-harmonic generation using the fundamental, quasi-TE polarized waveguide modes in a thin-film lithium niobate (TFLN) waveguide. Here, a shallow-etched ridge waveguide is fabricated in x-cut magnesium oxide doped TFLN and is poled accurately over 5 mm. The high fidelity of the poling is demonstrated over long lengths using a non-destructive technique of confocal scanning second-harmonic microscopy. We report a second-harmonic conversion efficiency of up to 939 %/W (length-normalized conversion efficiency 3757 %/Wcm²), measured at telecommunications wavelengths. The device demonstrates a narrow spectral linewidth (1 nm) and can be tuned precisely with a tuning characteristic of 0.1 nm/°C, over at least 40 °C without measurable loss of efficiency.
Keywords: Atomic and Molecular Physics; and Optics

Poling thin-film x-cut lithium niobate for quasi-phase matching with sub-micrometer periodicity - Zhao, Jie; Rüsing, Michael; Roeper, Matthias; Eng, Lukas M.; Mookherjea, Shayan (Journal of Applied Physics)
Quasi-phase-matched grating structures in lithium niobate waveguides with sub-micrometer periodicities will benefit the development of short-wavelength nonlinear optical devices. Here, we report on the reproducible formation of periodically poled domains in x-cut single-crystalline thin-film lithium niobate with periodicities as short as 600 nm. Shaped single-voltage poling pulses were applied to electrode structures that were fabricated by a combination of electron-beam and direct-writing laser lithography. Evidence of successful poling with good quality was obtained through second-harmonic microscopy and piezoresponse force microscopy imaging. For the sub-micrometer period structures, we observed patterns with a double periodicity formed by domain interactions and features with sizes <200 nm.
Keywords: General Physics and Astronomy

High Quality Entangled Photon Pair Generation in Periodically Poled Thin-Film Lithium Niobate Waveguides - Zhao, Jie; Ma, Chaoxuan; Rüsing, Michael; Mookherjea, Shayan (Physical Review Letters)
Keywords: General Physics and Astronomy

Periodic Poling of X-Cut Thin-Film Lithium Niobate: The Route to Submicrometer Periods - Rüsing, Michael; Roeper, M.; Amber, Z.; Kirbus, B.; Eng, L.M.; Zhao, J.; Mookherjea, S. (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Zwischen romantischem Fragment und Skizze/n der Moderne. Zum medialen Realismus von Wilhelm Raabes "Wer kann es wenden?" - Gretz, Daniela (Jahrbuch der Raabe-Gesellschaft)
Keywords: General Medicine

Towards Real-Time and Unsupervised Campaign Detection in Social Media - Assenmacher, D; Adam, L; Trautmann, Heike; Grimme, C (Proceedings of the Florida Artificial Intelligence Research Society Conference)
The detection of orchestrated and potentially manipulative campaigns in social media is far more meaningful than an- alyzing single account behaviour but also more challenging in terms of pattern recognition, data processing, and com- putational complexity. While supervised learning methods need an enormous amount of reliable ground truth data to find rather inflexible patterns, classical unsupervised learn- ing techniques need a lot of computational power to handle large amount of data. This makes them infeasible for real- time analysis. In this work, we demonstrate the applicability of text stream clustering for the real-time detection of coordi- nated campaigns.

Die Tageszeitung des 18. Jahrhunderts auf dem Weg zum Massenmedium - Wille, Manuel
In der Forschungsarbeit wird die Zeitungskommunikation des 18. Jahrhunderts aus sprachwissenschaftlicher Perspektive untersucht. Es wird gezeigt, wie sich das Textsortenrepertoire der Zeitung weiterentwickelte, welche sprachlichen Wandelprozesse stattfanden und wie die Zeitung übergreifend allmählich zu einem Massenmedium avancierte. Der textlinguistische Zugang auf die Zeitungssprache wird an den relevanten Stellen ergänzt durch einschlägige Erkenntnisse aus der historischen Presseforschung und der linguistischen Kulturanalyse. So wird etwa nachgezeichnet, wie sich die Zeitungsschreiber im Laufe des Jahrhunderts immer stärker von den Einflüssen der Kanzleisprachen lösten und Formulierungsstrategien etablierten, die auf die Anforderungen des journalistischen Berichtens abgestimmt waren. Mit diesen und weiteren Ergebnissen wird der Versuch angestellt, eine Forschungslücke der Sprachgeschichtsforschung zu schließen, in der die Zeitungen des 18. Jahrhunderts bisher lediglich randständig untersucht wurden.
Keywords: text linguistics; newspaper; Hamburgischer Correspondent; Textlinguistik; Sprachgeschichte; Textsortenwandel; Korpuslinguistik

Pressesprache - Wille, Manuel (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online, edited by Stefan J. Schierholz.)

Zeitungsstil - Wille, Manuel (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online, edited by Stefan J. Schierholz.)

So Far...From Now On # 6. - Jacke, Christoph (Die Aufhebung)

Statistical and Neural Network Based Speech Activity Detection in Non-Stationary Acoustic Environments - Heitkaemper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (INTERSPEECH 2020 Virtual Shanghai China)
Speech activity detection (SAD), which often rests on the fact that the noise is "more'' stationary than speech, is particularly challenging in non-stationary environments, because the time variance of the acoustic scene makes it difficult to discriminate speech from noise. We propose two approaches to SAD, where one is based on statistical signal processing, while the other utilizes neural networks. The former employs sophisticated signal processing to track the noise and speech energies and is meant to support the case for a resource efficient, unsupervised signal processing approach. The latter introduces a recurrent network layer that operates on short segments of the input speech to do temporal smoothing in the presence of non-stationary noise. The systems are tested on the Fearless Steps challenge database, which consists of the transmission data from the Apollo-11 space mission. The statistical SAD achieves comparable detection performance to earlier proposed neural network based SADs, while the neural network based approach leads to a decision cost function of 1.07% on the evaluation set of the 2020 Fearless Steps Challenge, which sets a new state of the art.
Keywords: voice activity detection; speech activity detection; neural network; statistical speech processing

When entrepreneurs become leaders: how entrepreneurs deal with people management - Hubner-Benz, Sylvia (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Hustlers, hipsters and hackers: Potential employees’ stereotypes of entrepreneurial leaders - Rudic, Biljana; Hubner-Benz, Sylvia; Baum, Matthias (Journal of Business Venturing Insights)
Keywords: Management of Technology and Innovation; Business and International Management

Perceptions of the Self Versus One’s Own Social Group: (Mis)conceptions of Older Women’s Interest in and Competence With Technology - Gales, Alina; Hubner-Benz, Sylvia (Frontiers in Psychology)
Keywords: General Psychology

Political embeddedness and firms’ choices of earnings management strategies in China - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin (Accounting & Finance)
Abstract We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms’ choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs’ total earnings management level is higher than that of non‐PCEs.
Keywords: Economics; Econometrics and Finance (miscellaneous); Finance; Accounting

Bringing Signaling Theory to Intermediated Voluntary Disclosure. Commentary on “Detecting False Accounts in Intermediated Voluntary Disclosure” by Patrick Callery and Jessica Perkins - Hahn, Rüdiger; Reimsbach, Daniel (Academy of Management Discoveries)

Enhancing Fifth Graders’ Awareness of Syntactic Features in Mathematical Word Problems: A Design Research Study on the Variation Principle - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik, 41(2))

Symmetry in optimal control: A multiobjective model predictive control approach - Flaßkamp, K.; Ober-Blöbaum, Sina; Peitz, S. (Advances in Dynamics, Optimization and Computation)

"Dein jüdisches Gesicht". Zu drei Gedichten des "Ilana"-Zyklus von Paul Celan - Spener, Anna Maria (Celan-Jahrbuch 11)

Automatisierung der motorischen Kontrolle - Krause, Daniel; Blischke, Klaus (Bewegung, Training, Leistung und Gesundheit)

Is it still worth it? Applying expectancy-value theory to investigate the intraindividual motivational process of forming intentions to drop out from university - Schnettler, Theresa; Bobe, Julia; Scheunemann, Anne; Fries, Stefan; Grunschel, Carola (Motivation and Emotion)
Abstract The intraindividual process of study dropout, from forming dropout intention to deregistration, is of motivational nature. Yet typical studies investigate interindividual differences, which do not inform about intraindividual processes. Our study focused on the intraindividual process of forming dropout intention, and applied expectancy-value theory to analyze its motivational underpinnings. To expand research, we considered associations of intraindividual deviations in expectancy, intrinsic value, attainment value, utility value, and cost to intraindividual deviations in dropout intention. A total of 326 undergraduate students of law and mathematics rated motivational variables and dropout intention three times from semester start to the final exam period. Multilevel regression analyses revealed that intraindividual changes in intrinsic value, attainment, and cost, but not in expectancy and utility, related to intraindividual changes in dropout intention. Further, we considered students’ demographics as moderators. Only age moderated the association between intrinsic value and dropout intention. Our results stress the crucial role of certain value components, including cost, for emerging dropout intention.
Keywords: Experimental and Cognitive Psychology; Social Psychology

End-to-End Training of Time Domain Audio Separation and Recognition - von Neumann, Thilo; Kinoshita, Keisuke; Drude, Lukas; Boeddeker, Christoph; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
The rising interest in single-channel multi-speaker speech separation sparked development of End-to-End (E2E) approaches to multispeaker speech recognition. However, up until now, state-of-theart neural network–based time domain source separation has not yet been combined with E2E speech recognition. We here demonstrate how to combine a separation module based on a Convolutional Time domain Audio Separation Network (Conv-TasNet) with an E2E speech recognizer and how to train such a model jointly by distributing it over multiple GPUs or by approximating truncated back-propagation for the convolutional front-end. To put this work into perspective and illustrate the complexity of the design space, we provide a compact overview of single-channel multi-speaker recognition systems. Our experiments show a word error rate of 11.0% on WSJ0-2mix and indicate that our joint time domain model can yield substantial improvements over cascade DNN-HMM and monolithic E2E frequency domain systems proposed so far.

Multi-Talker ASR for an Unknown Number of Sources: Joint Training of Source Counting, Separation and ASR - von Neumann, Thilo; Boeddeker, Christoph; Drude, Lukas; Kinoshita, Keisuke; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (Proc. Interspeech 2020)
Most approaches to multi-talker overlapped speech separation and recognition assume that the number of simultaneously active speakers is given, but in realistic situations, it is typically unknown. To cope with this, we extend an iterative speech extraction system with mechanisms to count the number of sources and combine it with a single-talker speech recognizer to form the first end-to-end multi-talker automatic speech recognition system for an unknown number of active speakers. Our experiments show very promising performance in counting accuracy, source separation and speech recognition on simulated clean mixtures from WSJ0-2mix and WSJ0-3mix. Among others, we set a new state-of-the-art word error rate on the WSJ0-2mix database. Furthermore, our system generalizes well to a larger number of speakers than it ever saw during training, as shown in experiments with the WSJ0-4mix database.

Gedenken an Luftangriffe auf Paderborn: "Erinnerung wird nie obsolet sein" - Hartung, Olaf (Neue Westfälische)

Workshops zur geschichtsdidaktischen Lehre in Zeiten von Corona - Hartung, Olaf (Paderborner Universitätszeitschrift)

Deep Neural Network based Distance Estimation for Geometry Calibration in Acoustic Sensor Network - Gburrek, Tobias; Schmalenstroeer, Joerg; Brendel, Andreas; Kellermann, Walter; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))
We present an approach to deep neural network based (DNN-based) distance estimation in reverberant rooms for supporting geometry calibration tasks in wireless acoustic sensor networks. Signal diffuseness information from acoustic signals is aggregated via the coherent-to-diffuse power ratio to obtain a distance-related feature, which is mapped to a source-to-microphone distance estimate by means of a DNN. This information is then combined with direction-of-arrival estimates from compact microphone arrays to infer the geometry of the sensor network. Unlike many other approaches to geometry calibration, the proposed scheme does only require that the sampling clocks of the sensor nodes are roughly synchronized. In simulations we show that the proposed DNN-based distance estimator generalizes to unseen acoustic environments and that precise estimates of the sensor node positions are obtained.

Corporate Entrepreneurship: Die Rolle und Bedeutung des Humankapitals - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Corporate Entrepreneurship durch die Allokation von Ressourcen - Megow, N.; Kabst, Rüdiger (Perspektiven des Entrepreneurships: Unternehmerische Konzepte zwischen Theorie und Praxis)

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie; Furman, Susanne; Acar, Yasemin

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie M.; Furman, Susanne M.; Acar, Yasemin (HCI for Cybersecurity, Privacy and Trust)

Cloudy with a Chance of Misconceptions: Exploring Users’ Perceptions and Expectations of Security and Privacy in Cloud Office Suites - Wermke, Dominik; Huaman, Nicolas; Stransky, Christian; Busch, Niklas; Acar, Yasemin; Fahl, Sascha (Sixteenth Symposium on Usable Privacy and Security, SOUPS 2020, August 7-11, 2020)